2003
DOI: 10.1037/1099-9809.9.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identity and the MMPI in African American Male College Students.

Abstract: The relation of the Minnesota Multiphasic Personality Inventory (MMPI) to the Racial Identity Attitude Scale--Black, Short Form (RIAS-B) was examined among 50 African American male college students in a reanalysis of unpublished MMPI data described in R. H. Dana (1993). This permitted study of relationships between MMPI scores and specific psychological variables hypothesized to produce cultural differences among African Americans. Results indicated RIAS-B scale scores functioned as predictors of MMPI scale sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…A comparison of means and standard deviations from our study with those of other samples using the same measures indicated that our sample was within half a standard deviation of Black college men on Pre-Encounter and Internalization scores (Whatley, Allen, & Dana, 2003) and within half a standard deviation of mostly White college men on the CMNI Total score (Mahalik, Locke, et al, 2003), self-esteem scores (Cournoyer & Mahalik, 1995), and GSI scores (Todd, Deane, & McKenna, 1997). Our sample was lower but within one standard deviation of Black college men on Immersion-Emersion scores (Whatley et al, 2003).…”
Section: Preliminary Analysesmentioning
confidence: 86%
See 1 more Smart Citation
“…A comparison of means and standard deviations from our study with those of other samples using the same measures indicated that our sample was within half a standard deviation of Black college men on Pre-Encounter and Internalization scores (Whatley, Allen, & Dana, 2003) and within half a standard deviation of mostly White college men on the CMNI Total score (Mahalik, Locke, et al, 2003), self-esteem scores (Cournoyer & Mahalik, 1995), and GSI scores (Todd, Deane, & McKenna, 1997). Our sample was lower but within one standard deviation of Black college men on Immersion-Emersion scores (Whatley et al, 2003).…”
Section: Preliminary Analysesmentioning
confidence: 86%
“…Our sample was lower but within one standard deviation of Black college men on Immersion-Emersion scores (Whatley et al, 2003).…”
Section: Preliminary Analysesmentioning
confidence: 96%
“…Finally, diagnostic instruments that are used to assess symptoms may be culturally biased (Adebimpe, 1981). In a study of 50 AA male college students who were given the Minnesota Multiphasic Personality Inventory (MMPI) and the Racial Identity Attitude Scale-Black, Short-Form (RIAS-B), scores on the RIAS-B that indicated normative racial identity were associated with MMPI scales for antisocial personality attributes (P = .012; Whatley et al, 2003).…”
Section: Provider Influence or Bias In Diagnosismentioning
confidence: 99%
“…se discuten las implicaciones para la investigación y la consejería. R acial identity is now a widely accepted construct within the psychological literature and has been associated with an array of variables ranging from intrapsychic processes, such as self-esteem and personality (Mumford, 1994;Whatley, Allen, & Dana, 2003), to cognitively based outcomes, such as academic performance and perceptions of counselors (Want, Parham, Baker, & Sherman, 2004). Given that racial identity statuses are considered to be an aspect of personality (Carter, 1995), it is reasonable to assume that racial identity statuses would be related to various types of emotional states, social beliefs, and aspects of psychosocial competence (Carter, DeSole, Sicalides, Glass, & Tyler, 1997;Carter, Helms, & Juby, 2004).…”
mentioning
confidence: 99%